Screening for Borderline Personality Disorder (BPD) in Malaysia: a validation study of the McLean Screening Instrument for BPD - Keng, Shian Ling; Mohd Salleh Sahimi, Hajar; Chan, Lai Fong; Tan, Kit Aun; Vafa, Samira; Zainal, Nur Hani; Woon, Luke Sy Cherng; Sim, Su Hua; Wong, Man Kuan; Eu, Choon Leng (BioMed Central, 2025)
Background: Borderline personality disorder (BPD) is often underdiagnosed in Malaysia due to limited specialized training and validated screening tools. Although the McLean Screening Instrument for BPD (MSI-BPD) is a well-established measure, it lacks validation in Southeast Asia. This study evaluated the MSI-BPD’s psychometric properties in a Malaysian context. Methods: Two samples, including a clinical sample of psychiatric outpatients (N = 101; mean age = 28.02 years; 74.3% female) and a healthy control group (N = 314; mean age = 29.75 years; 74.8% female), were recruited from a public hospital in Kuala Lumpur, Malaysia and a private university in Malaysia, respectively. Participants in the clinical sample completed the MSI-BPD along with other self-report psychological symptom measures, and BPD diagnoses were confirmed through a semi-structured clinical interview. Psychometric analyses were conducted on the clinical sample to assess the scale’s internal consistency, convergent and discriminant validity, factor structure, and predictive validity concerning BPD diagnosis. Both the clinical and healthy control samples were included in a known-groups validity analysis to further evaluate the scale. Results: The MSI-BPD exhibited good internal consistency (Cronbach’s α = 0.82) and convergent validity, as evidenced by significant correlations with related psychological symptoms. The scale also demonstrated good discriminant validity and predictive accuracy (area under the curve = 0.91), with an optimal cut-off score of 8. Confirmatory factor analyses supported a four-factor model (with factors identified being affective disturbances, impulsivity, unstable relationships, and disturbed cognition) as the best fit among the five evaluated models. The study also established the known-groups validity of the MSI-BPD, demonstrating its ability to distinguish clinical samples from healthy controls, with clinical participants scoring significantly higher than controls. Conclusions: The MSI-BPD is a valid and reliable tool for screening BPD in Malaysia. The findings enhance our understanding of BPD’s construct validity and factor structure in Southeast Asia, which leads to a more universal and cross-cultural understanding of BPD. Validating the screening instrument is crucial for improving mental health assessments and interventions, as well as strategies to better identify individuals at-risk for BPD for early intervention optimizing outcomes in a low-resource Southeast Asian context.